The La Salle Green Hills Grade School faculty evaluation program: an analysis - Alcanites, Juliana Caracta (Animo Repository, 1984)
This study endeavored to explore the grade school faculty evaluation program of La Salle Green Hills with an end in view of describing and evaluating the entire evaluation program evaluating and improving the end-of-the-year evaluation instrument. The research study is divided into three main areas of concern namely, program description, program awareness and perception, and instrument evaluation. Specifically it is concerned with the attainment of these objectives: To describe the faculty evaluation program in terms of its basic rationale, major assumptions, main objectives, and evaluation procedures. To analyze the teachers' level of awareness of the entire evaluation process and their perception of its importance and effectivity as implemented at LSGH. To analyze the end-of-the-year evaluation instrument with four component scales in order to determine its content validity and reliability. In describing the faculty evaluation program, data were gathered from existing school documents and interviews of some grade school teachers and administrators. In analyzing the program, an original questionnaire was developed to determine the teachers' awareness of the program, their perception of its importance and effectivity. The respondents were 72 grade school teachers still in active service for SY 1983-1984 who have knowledge about the program. The grade or unit 5 teachers who were exposed to another evaluation scheme on an experimental basis were not part of the study. In evaluating the instrument, only the end-of-the-year instrument used from SY 1978- 79 to SY 1982-83 were included. Since there were other rating scales used by the other grade levels in a desire to improve the existing instrument, only those merit ratings in SY 1982-83 based on these end-of-the-year forms were item analyzed. The teachers' awareness of the school's evaluation program which was covered in the Scale B of the questionnaire was determined by getting the percentage response to each statement. The extent of importance and effectivity which was included in Scales A and C, respectively, in the questionnaire was determined by using the Likert scaling technique. The mean scores of Scales A and C were compared and contrasted by using the Corrective Action Priority Index (CAPI) to initiate a closer attention on items deemed important but not implemented effectively. To estimate the reliability of the end-of-the-year instrument the formula used was Cronbach's coefficient alpha based on the mean square for subjects and interaction or residual in one-way repeated measure design. Besides obtaining the reliability coefficient for each subscale, an item analysis was made by computing the item to subscale correlation and item to total component scale correlation. Experts in the field of faculty evaluation and test construction were requested to analyze the content validity of the instrument.